2021
DOI: 10.1111/jdi.13489
|View full text |Cite
|
Sign up to set email alerts
|

Association of non‐alcoholic fatty liver disease with diabetic retinopathy in type 2 diabetic patients: A meta‐analysis of observational studies

Abstract: Aims/Introduction Non‐alcoholic fatty liver disease (NAFLD) is becoming more and more prevalent in type 2 diabetes mellitus. Evidence connecting NAFLD to diabetic retinopathy (DR) is increasing, but the results vary. Thus, we undertook a meta‐analysis to explore the effect of NAFLD on diabetic retinopathy in patients with type 2 diabetes mellitus. Materials and Methods PubMed, Embase, Cochrane and Scopus database were searched for until September 30, 2019. Original studies analyzing the association between NAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
2
31
1
Order By: Relevance
“…Fetuin-A has also been found to accelerate incorporation of exogenous fatty acids into cellular triglycerides and cholesterol efflux from cells [ 7 ], yet no substantial correlation between fetuin-A and cholesterol or triglycerides could be observed in our study, and the adjustment for these confounders did not essentially alter the estimates. Some studies suggested increased levels of fetuin-A in NAFLD [ 36 ], inverse [ 39 , 40 ] or positive associations [ 41 , 42 ] between NAFLD and vascular complications in diabetes patients. We did not detect any effect modification by FLI, and fetuin-A only weakly correlated with FLI.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuin-A has also been found to accelerate incorporation of exogenous fatty acids into cellular triglycerides and cholesterol efflux from cells [ 7 ], yet no substantial correlation between fetuin-A and cholesterol or triglycerides could be observed in our study, and the adjustment for these confounders did not essentially alter the estimates. Some studies suggested increased levels of fetuin-A in NAFLD [ 36 ], inverse [ 39 , 40 ] or positive associations [ 41 , 42 ] between NAFLD and vascular complications in diabetes patients. We did not detect any effect modification by FLI, and fetuin-A only weakly correlated with FLI.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD affects more than 25% of the global population [ 20 ] and is largely demonstrated as highly prevalent in patients with T2DM (60–75%) [ 21 ]. Many studies proved that NAFLD is associated with an increased risk of macro- and micro-vascular complications in diabetic patients [ 22 , 23 , 24 ], notably including albuminuria [ 25 ] and retinopathy [ 26 ]. Currently, there is little information about the association between NAFLD and DPN, and the available data are scarce and conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Some cross-sectional studies have investigated the relationship between NAFLD (as detected by imaging techniques) and the risk of prevalent diabetic retinopathy in patients with T2DM, reporting inconsistent results [44,51]. In this regard, a 2021 metaanalysis of nine cross-sectional studies for a total of 7170 patients with T2DM (57% with NAFLD on ultrasonography) reported no association between NAFLD and risk of prevalent diabetic retinopathy (random-effects odds ratio 0.94, 95% confidence interval 0.51-1.71; I 2 = 96%) [52]. In addition, in that meta-analysis, subgroup analyses suggested that in China, Korea and Iran, T2DM patients with NAFLD had a decreased risk of diabetic retinopathy when compared with those without NAFLD, whereas in Italy and India, T2DM patients with NAFLD had an increased risk [52].…”
Section: Diabetic Retinopathymentioning
confidence: 99%